2020
DOI: 10.1002/bjs.12028
|View full text |Cite
|
Sign up to set email alerts
|

Central lymph node dissection and permanent hypoparathyroidism after total thyroidectomy for papillary thyroid cancer: population-based study

Abstract: Background Papillary thyroid cancer is treated with total/near-total thyroidectomy (TT) with or without central lymph node dissection (CLND), depending on risk factors and tumour size. Balancing the risk of disease recurrence and surgical morbidity remains a challenge. A population-based nationwide study was undertaken to evaluate the risk of permanent hypoparathyroidism associated with CLND. Method Data on patients with stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…This study identified a six-month post-surgical hypoparathyroidism or hypocalcaemia rate of 10.4 per cent, with the incidence rising to 19.8 per cent in those who had an inadvertent parathyroidectomy. The high incidence of sixmonth post-surgical hypoparathyroidism or hypocalcaemia in this cohort may be explained by the relatively high rate of central neck dissection (an independent risk factor for permanent hypoparathyroidism), 30 and the criteria used to define six-month post-surgical hypoparathyroidism or hypocalcaemia (patients requiring calcium or vitamin D supplements at six months).…”
Section: Inadvertent Parathyroidectomy and Post-surgical Hypoparathyr...mentioning
confidence: 95%
“…This study identified a six-month post-surgical hypoparathyroidism or hypocalcaemia rate of 10.4 per cent, with the incidence rising to 19.8 per cent in those who had an inadvertent parathyroidectomy. The high incidence of sixmonth post-surgical hypoparathyroidism or hypocalcaemia in this cohort may be explained by the relatively high rate of central neck dissection (an independent risk factor for permanent hypoparathyroidism), 30 and the criteria used to define six-month post-surgical hypoparathyroidism or hypocalcaemia (patients requiring calcium or vitamin D supplements at six months).…”
Section: Inadvertent Parathyroidectomy and Post-surgical Hypoparathyr...mentioning
confidence: 95%
“…Similar results also have been observed in a large series of 1087 patients submitted to thyroidectomy alone, or thyroidectomy plus ipsilateral or bilateral CLND, in which the authors demonstrated that bilateral CLND had a significantly higher rate of permanent hypoparathyroidism [ 24 ]. Recently, Salem et al also demonstrated that CLND was a risk factor for permanent hypoparathyroidism (OR = 3.74, IC 95% [1.46–9.59]), based on the use of combined therapy 6 months after surgery [ 25 ]. Interestingly, they also found that node negativity was associated with a risk of permanent hypoparathyroidism (OR = 3.08, IC 95% [1.31–7.25]), suggesting that an extensive exploration of the central neck compartment might increase the risk of unintentional removal of the lower parathyroid glands.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic level VI lymph node dissection is associated with a higher incidence of recurrent laryngeal nerve damage and long-term permanent hypoparathyroidism. 1054 It is therefore not routinely recommended, but it may be indicated in individuals with high-risk tumours.…”
Section: Management Of Differentiated Thyroid Carcinomamentioning
confidence: 99%